Analisis Variasi Rekonstruksi Increment Overlapping terhadap Informasi Citra Anatomi pada Pemeriksaan MSCT Nasofaring dengan Klinis Karsinoma - Jeffri Ardiyanto; Darmini Darmini; Widiya Purnama Sari (Jurnal Imejing Diagnostik (JImeD), 2017)
Background: In Nasopharyngeal MSCT examination, the radiologist wants optimal image  in order to evaluate the characteristics of the tumor, bone destruction due to a tumor, the extent of tumor invasion and the detection of regional metastases that serve as guidelines in determining the clinical stage in patients with nasopharyngeal carcinoma. So setting the scan parameters rekostruksi increments during the process multiplanar reconstruction (MPR)   image on  Nasopharyngeal MSC T will produce optimal images for diagnosis enforcement. Overlapping reconstruction increment is the distance between the image that has been reconstructed on the data volume that is made smaller than the size of the slice thickness is used. Selection of the reconstruction value increment overlapping usage right has an advantage in generating image anatomical information better for image noise becomes lower and accurate for diagnosing small structures, especially of hidden nasopharynx anatomy  and difficult to detect. The purpose of this study was to determine the influence variation reconstruction increment overlapping to the anatomical information image on nasopharyngea MSCT l examination with the carcinoma  clinical and determine the best value reconstruction increment overlapping that can provide optimal anatomical information image on nasopharyngeal MSCT examination with the clinical of carcinoma.Methods: This research was quantitative research with pre-experimental approach with one shoot case study method. This research was carried out by means of SIEMENS "SOMATOM EMOTION" - 16 slice in Installing Radiodiagnostic Hospital Dr. Soetomo Surabaya . The data in the form of a data volume of 10 patients in the sample with setting 3 mm slice thickness and reconstruction increment given the variation of the overlapping 30% of slice thickness (0.9 mm), 40% of the slice thickness (1.2 mm) and 50% of the slice thickness (1.5 mm) on MSCT nasopharyngeal examination with the clinical of carcinoma. Assessment anatomical information performed by the two respondents or reviewer. The data analysis was  testing the influence with  the simple  linear regression  tets and to determine the value of  reconstruction increment overlapping optimal use friedman mean rank test.Result: The results showed a influence of variation reconstruction increment overlapping to the anatomical information image on nasopharyngeal MSCT examination with the clinical of carcinoma with a significance level of p = 0,000 (p 0.05). The best value reconstruction increment overlapping that can provide optimal anatomical information image on MSCT nasopharyngeal examination with the clinical of carcinoma is a reconstruction increment overlapping 50% of the slice thickness 3 mm (1.5 mm) with a mean rank in the axial slice and coronal slice image of 2.61.Conclution: There are influence of variation reconstruction increment overlapping to the anatomical information image on MSCT nasopharyngeal examination with the clinical of carcinoma with a significance level of p = 0,000 (p 0.05). Reconstruction increment overlapping 50% of the slice thickness 3 mm (1.5 mm) is a best value that can provide optimal anatomical information image on  nasopharyngeal MSCT examination with the clinical of carcinoma.